Definitive Repair of Injuries to the Liver During Initial Trauma Laparotomy. Issue 8 (August 2021) - Hashavia, Eyal; Goldstein, Adam Lee; Nachmany, Ido; Shimonov, Abigail; Klausner, Joseph M.; Soffer, Dror
Introduction: Numerous surgical approaches and hemostatic techniques are used and have been described when operating on the traumatized liver. Despite a substantial decline in operative liver trauma, there still remains a debate on the optimal surgical approach, and goals, during the initial trauma laparotomy. Hepatic resection during the first operation, including the damage control settings, is advocated and practiced in only a select few institutions and remains highly controversial. Here, we describe our success with hepatic resection, repair, and/or hepatic vascular repair, during the trauma laparotomy with our emphasis on the collaboration between the trauma and hepatobiliary surgical teams. Case Series: From 207 patients with liver injuries during the study period, 7 patients had definitive liver resection or repair during the initial trauma laparotomy. One had hepatic tissue repair, 1 had hepatic vein repair, and 5 had liver resections. All the operations involved a hepatobiliary surgeon together with the trauma team. There were no fatalities in the liver operation group, no sepsis, or need for emergent angiography because of hemorrhage. Four patients needed endoscopic retrograde cholangiopancreatography (ERCP) and stenting because of biliary leak. Three patients were discharged home and 4 to rehabilitation. Discussion: Hepatic resection, and/or definitive hepatic repair, may be safe and beneficial to the patients during the initial operation even in a damage control setting when the patients' overall condition allows. We emphasize the benefit of collaboration with experienced and trained liver surgery, especially in lower volume trauma centers. ERCP is commonly needed for postoperative biliary leak and should be readily utilized.